THE PRACTICAL SIGNIFICANCE OF FORMING PROFESSIONAL COMPETENCES IN TECHNOLOGY LESSONS OF PRIMARY CLASS STUDENTS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
In this article, the practical importance of forming professional competences of primary school students in technology lessons is highlighted in different ways.